Diagnostic value of immune indicators and cytokines in sepsis after percutaneous nephrolithotomy (PCNL): Immune indicators and cytokines in sepsis after PCNL - Jin, Yiheng; Li, Yamei; Zhang, Xiaoyu; Han, Bing; Yan, Xingshi (Journal of Medical Biochemistry, 2025)
Objective: To analyze the changes in and diagnostic value of immune indicators and cytokines in patients with sepsis after percutaneous nephrolithotomy (PCNL). Methods: Clinical information was gathered from 405 calculi patients who underwent PCNL at our facility between January 2021 and December 2024. The patients were divided into a sepsis group (12 patients) and a nonsepsis group (393 patients) on the basis of whether sepsis occurred after the operation. The levels of CD4+/CD8+ cells, the neutrophil-to-lymphocyte ratio (NLR), soluble trigger receptor-1 (sTREM-1) in myeloid cells, procalcitonin (PCT), tumor necrosis factor α (TNF-α), and interleukin-6 (IL-6) were measured in the two patient groups. The predictive value of the above indicators for sepsis was analyzed via receiver operating characteristic (ROC) curves. Results: The number of patients with staghorn calculi in the sepsis group was greater than that in the nonsepsis group (P<0.05). The NLR and sTREM-1 level were greater in the sepsis group than in the nonsepsis group (all P<0.05), and the CD4+/CD8+ ratio was lower in the sepsis group than in the nonsepsis group (P<0.05). The levels of serum IL-6, TNF-α and PCT in the sepsis group were greater than those in the nonsepsis group (all P<0.05). The area under the curve (AUC) for the combined prediction of sepsis after PCNL by each index was 0.996, with a predictive sensitivity of 91.3% and a specificity of 98.4%. Conclusion: The NLR, sTREM-1, IL-6, TNF-α and PCT in patients with sepsis after PCNL increased, whereas the CD4+/CD8+ ratio decreased. The combined detection of these levels is beneficial for guiding the early clinical prediction of the occurrence of postoperative sepsis in patients with PCNL.